2011
DOI: 10.1002/chem.201100287
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Unnatural Somatostatin Analogues through Bioorthogonal Iodo‐ and Ethynyl‐Disulfide Intercalators

Abstract: Iodo- and ethynyl-containing bisalkylating bioconjugation agents 5 and 8 were achieved and allow the introduction of reactive unnatural substituents into proteins and peptides whilst the bioactive 3D structure is retained. Derivatives of the peptide hormone somatostatin bearing a single iodo or ethynyl group were prepared through intercalation into the disulfide bridge. For the first time, the exact reaction mechanism of the intercalation was elucidated by applying 2D NMR experiments and it was shown that, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…From the findings of these earliest reagents, some of the key steps and criteria in disulfide modification can be summarized as follows: 1) the “activation” of the disulfide by reduction to release two active cysteines for reaction, 2) followed by a fast addition reaction of the reagent “R” (Figure ) with one reduced thiol group to minimize unfolding, aggregation or disulfide scrambling, and most critically, 3) the second rebridging step of the other proximal cysteine residue to retain the 3D structure and function of the protein. In order to preserve the tertiary structure, potential irreversible denaturation and aggregation of the proteins need to be minimized, and disulfide scrambling reactions should be avoided as well in the case that more than one disulfide is reduced . Site‐selectivity is finally achieved by: 1) examination of solvent accessible disulfides from the protein structure, and 2) stoichiometric control of the disulfide rebridging reagent used .…”
Section: Disulfide Rebridging Agents: Syntheses Features and Biocmentioning
confidence: 99%
See 3 more Smart Citations
“…From the findings of these earliest reagents, some of the key steps and criteria in disulfide modification can be summarized as follows: 1) the “activation” of the disulfide by reduction to release two active cysteines for reaction, 2) followed by a fast addition reaction of the reagent “R” (Figure ) with one reduced thiol group to minimize unfolding, aggregation or disulfide scrambling, and most critically, 3) the second rebridging step of the other proximal cysteine residue to retain the 3D structure and function of the protein. In order to preserve the tertiary structure, potential irreversible denaturation and aggregation of the proteins need to be minimized, and disulfide scrambling reactions should be avoided as well in the case that more than one disulfide is reduced . Site‐selectivity is finally achieved by: 1) examination of solvent accessible disulfides from the protein structure, and 2) stoichiometric control of the disulfide rebridging reagent used .…”
Section: Disulfide Rebridging Agents: Syntheses Features and Biocmentioning
confidence: 99%
“…Thereafter, the second thiol group in close vicinity undergoes a subsequent Michael addition with the concomitant formation of a three‐carbon bridge to yield the bisthioether (Scheme B). The mechanism of disulfide rebridging by bis‐sulfones has been further elucidated by NMR spectroscopy and it has been shown that diastereomers are formed . In the absence of thiol groups, side reactions with water can occur at basic pH (>8) due to the reactivity of the alkene group in the monosulfone, and thus such high pH should be avoided.…”
Section: Disulfide Rebridging Agents: Syntheses Features and Biocmentioning
confidence: 99%
See 2 more Smart Citations
“…[5] An interesting exception are the so-called equilibrium transfer alkylating crosslinking (ETAC) reagents introduced in the 1970s by Lawton and co-workers for the dynamic cross-linking of biomolecules. [6,7] These reagents reversibly form covalent bonds between pairs of accessible nucleophilic sites on proteins through a series of inter-and intramolecular Michael and retro-Michael reactions until the most thermodynamically stable crosslink is located (Scheme 1 a). [6a] We wondered whether it would be possible to apply a similar concept, focusing instead on chemistry where the cross-linked products are less stable than those attached by a single covalent bond, to make synthetic small molecules that migrate with a high degree of processivity [8] along a linear molecular track.…”
mentioning
confidence: 99%